Genetic Methods and Tools for Managing Crop Pests - Chakravarthy, A. K. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This contributed volume aims at bringing together all the genetic engineering tools for managing various types of crop pests. The main focus of this book is to explore the application of these tools in pest management. Major pest groups covered in this book are insects, mites and nematodes. The first section covers all major genetic tools and molecular approaches. The second section deals with genetic tools for of beneficial containing three chapters involving honey bees, silkworms and natural enemies. Next section deals with genetic interactions against pests in diverse geographical regions with special focus on Africa, Vietnam and Sri Lanka. Sections four and five addresses diverse aspects as management of pests, genetic behavior, gene expression, plasticity, pathways and interactions and options for mitigation of pests. It serves as a useful resource for professionals in the fields of entomology, agronomy, horticulture, ecology, and environmental sciences, as well as to agricultural producers and plant biotechnologists. .
Chapter 1. Newer Genetic Tools, Techniques, Vectors, Promoters and Molecular Markers for Genetic Engineering of Herbivorous Insects -- Chapter 2.Innovative Molecular Approaches for Pest Management -- Chapter 3. Modern Molecular Tools for Insect Diagnostics -- Chapter 4. Artificial Intelligence, Machine Learning and IOT in Pest Management -- Chapter 5. Genetic Tools for Integrated Management of Pests on Honey Bees in the Tropics -- Chapter 6. Genetics and Genomics of Bombyx mori L -- Chapter 7. Enhancing Genetic Efficiency of natural Enemies of Crop Pests -- Chapter 8. Application of Genetic Engineering Technologies to Manage Crop Pests and Diseases in Vietnam -- Chapter 9. Advances, Prospects and Limitations of Genetic Tools for Pest Management Strategies in Sri Lanka -- Chapter 10. Management of Pests Using Genetic Tools in Africa -- Chapter 11. Genetic Tools for the Management of Phytophagous Mites -- Chapter 12. Management of Potato Cyst Nematode (Globodera sp.) Using Biotechnological Approaches -- Chapter 13.Genetic and Molecular Approaches for Management of Potato Viral Diseases and their Vectors. Chapter 14. Genetic variation and Molecular ools for the Management of Brinjal Shoot and Fruit Borer Leucinodes orbonalis Guenée (Lepidoptera: Crambidae) -- Chapter 15. Management of Noctuid Pests using Genetic Tools -- Chapter 16. Genetics and Management of Pest Fruit Flies -- Chapter 17. Molecular Insights into Wing Polymorphism and Migration Patterns of Planthoppers -- Chapter 18. Genetic Engineering Technologies for Management of Crambid Pests -- Chapter 19.Intervention of Modern Genetic Tools for Managing Insect Pests of Fruit Crops -- Chapter 20.Advanced Molecular Diagnostic Tools for Longhorn Beetles -- Chapter 21.Molecular Characterization and Genetic Interventions in an Invasive Spiralling Whitefly Aleurodicus dispersus Russell -- Chapter 22.Recent Genetic Tools for the Management of Stored Product Pests -- Chapter 23.Genetic Tools for Insecticide Resistance Management -- Chapter 24.Genetic improvement of pigeon-pea(Cajanus cajan(L.) Millsp.) and Insect Resistance: strategies and achievements -- Chapter 25.Bruchid Resistance Studies in Blackgram Using Molecular Tools -- Chapter 26.Inducing Insect Resistance in Sesame by Innovative Genetic Manipulation using Mutagens -- Chapter 27.Advances in Insect Resistance Breeding Against Brown Planthopper and Gallmidge in Rice -- Chapter 28.Adoption of Molecular Tools for Combatting the Arthropod Pests.
Keywords: Plant diseases; Agriculture; Agricultural genome mapping; Agricultural biotechnology; Genetics; Plant Pathology; Agriculture; Agricultural Genetics; Agricultural Biotechnology; Genetics and Genomics